Waterloo great battles series - Forrest, Alan 1945- (Great battles, 2015)
Waterloo was the last battle fought by Napoleon and the one which finally ended his imperial dreams. It involved the deployment of huge armies and incurred heavy losses on both sides; for those who fought in it, Dutch and Belgians, Prussians and Hanoverians as well as British and French troops, it was a murderous struggle. It was a battle that would be remembered very differently across Europe. In Britain it would be seen as an iconic battle whose memory would be enmeshed in British national identity across the following century. In London news of the victory unleashed an outburst of patriotic